1995
DOI: 10.1007/bf01244854
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular detection of solvent vapours with calixarenes: Mass-sensitive sensors, molecular mechanics and BET studies

Abstract: Abstract. Chemical sensors, based on highly mass sensitive QMB or SAW devices, coated with thin layers of calixarenes, enable the detection of organic solvent vapours, especially halogenated or aromatic hydrocarbons, down to a few ppm. Force field calculations allow the tailoring of these sensor materials seeing that the predicted interaction energies between the host molecules and a large variety of analytes are linearly correlated to the measured sensor effects. These correlations and also BET adsorption ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 15 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…356,403 However, selectivity response patterns of cavitands to small molecules can be similar to common amorphous polymers 404 indicating that cavitand sensors can respond not solely only to molecules with an ideal fit in the cavity but also to sorbed molecules occupying both intracavity and intercavity sites. 96,405407 Nevertheless, the presence of a preorganized cavity in cavitands does promise an advantage in sensitivity compared to amorphous polymers, especially if applied to the sensor in multilayers. 406 …”
Section: Integration Of Sensing Materials With Transducersmentioning
confidence: 99%
“…356,403 However, selectivity response patterns of cavitands to small molecules can be similar to common amorphous polymers 404 indicating that cavitand sensors can respond not solely only to molecules with an ideal fit in the cavity but also to sorbed molecules occupying both intracavity and intercavity sites. 96,405407 Nevertheless, the presence of a preorganized cavity in cavitands does promise an advantage in sensitivity compared to amorphous polymers, especially if applied to the sensor in multilayers. 406 …”
Section: Integration Of Sensing Materials With Transducersmentioning
confidence: 99%
“…The results indicated that the size of the attached alkyl chain did not influence the complexation properties but deep cavity cavitands selectively discriminated between xylene isomers based on their shape.52 In a further study that correlated both theoretical and experimental results, Dickert and Schuster showed that thin films of 61 gave a large response to toluene vapours. 54 This was thought to be due to CH -x interactions between the host and guest respective alkyl and aromatic sites. The results also showed that the selective recognition of analytes by the thin films was due mainly to host/guest inclusion interactions.54 In a later report Dickert et al reports the detection of solvent vapours at concentrations as low as 2 .…”
Section: Binding Of Organic Amines From Aqueous Solution By Thin Filmmentioning
confidence: 99%
“…This shape enables calixarenes to act as effective receptors as a result of their natural cavities. Favorable host cavities are essentially formed by cyclic intramolecular hydrogen bonding of the hydroxyl groups to create the cup or cone shape of the calixarene [97]. Researchers have found it possible to control the host selectivity to ion or small-molecule binding by functional modification of the upper and lower rims [96].…”
Section: Calixarenesmentioning
confidence: 99%
“…Using calixarenes with multiple different functional groups incorporated on the lower rim has shown that the photophysical properties of these systems can be easily influenced by different target binding modes. Aside from chromogenic sensors, these biomimetic receptor materials have shown successful incorporation into a variety of sensor platforms, including quartz crystal microbalance and surface acoustic wave oscillator base sensors, as the selective coatings [97]. The shape and chiral selective capabilities of calixarene-based coatings have shown to offer a solution to the selectivity problem of several sensing platforms.…”
Section: Calixarenesmentioning
confidence: 99%